STAN NIETRZEŹWOŚCI JAKO „AFEKT” W RZYMSKIM PRAWIE KARNYM? - Kubiak, Przemysław (Zeszyty Prawnicze, 2016)
Drunkenness – a “Passion” in Roman Criminal Law? Summary Since ancient times jurists and lawyers have had to handle offences connected with alcohol abuse. There are only three texts on drunkenness in the Roman legal sources: two relate to offences committed by inebriate soldiers, and the third contains the basic division into intentional offences, accidental offences, and crimes of passion. In all three categories drunkenness was a mitigating factor, which may be surprising for modern lawyers. Other Roman sources present public opinion on drinking, which seems to have depended on the circumstances – heavy drinking and alcoholism were disapproved of. A precise analysis of the rhetorical writings shows elaborate distinctions between intentional and unintentional acts. Drunkenness was regarded as an emotional state which could influence the penalty, but the specific circumstances of the offence were crucial. The rhetorical works confirm the views presented in poetry and philosophy. Contrary to the legal sources, the facts seem to show that a judge could sentence an offender to a severe or mild punishment, or even acquit him if drunkenness had been a factor contributing to the offence. The rhetorical works may be considered to provide not only an important theoretical background to the legal sources, but also crucial supplementary information giving a better insight into Roman criminal law.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />